The crystal structure of catena-poly(bis(μ 2-chlorido)- (μ 2-4′-(pyridin-4-yl)-2,2′:6′,2″-terpyridine–N′, N″, N‴:N″″) -chlorido-dicopper(I,II)) monohydrate, C20H16N4OCl3Cu2 - Wang Yu-Qing; Gong Xiao-Jie; Xie Long-Chen; Chen Bao-Kuan (Zeitschrift für Kristallographie - New Crystal Structures)
C20H16N4OCl3Cu2, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 8.2232(13) Å, b = 10.8897(18) Å, c = 11.3838(19) Å, α = 93.394(5)∘, β = 94.248(5)∘, γ = 91.588(5)∘, V = 1013.6(3) Å3, Z = 2, Rgt (F) = 0.0445, wRref (F 2) = 0.1203, T = 273 K.